Detecting and Locating a Changed Segment in a Binomial Sequence: Comparison - Zuokas, D. (Nonlinear Analysis: Modelling and Control, 2005)
A class of tests for testing a changed segment in a binomial sequence is proposed and an asymptotic behavior is established. A consistent procedure of estimating the length of a changed segment is proposed. The performance of two tests from the given class is compared by Monte-Carlo simulations. The results are applied for the non-coding deoxyribonucleic acid (DNA) sequence analysis.
Keywords: binomial random variables; changed segment; cumulative sums; DNA sequence analysis; epidemic alternative